Tracking Labor Demand with Online Job Postings: The Case of Health IT Workers and the HITECH Act. Issue 4 (9th September 2013) - Schwartz, Aaron; Magoulas, Roger; Buntin, Melinda
Abstract : Growth in the health information technology (health IT) workforce will be necessary for the widespread adoption of electronic health records called for by the Health Information Technology for Economic and Clinical Health (HITECH) provisions of the American Recovery and Reinvestment Act. However, the health IT workforce is difficult to track using existing sources of data. We introduce a novel method for measuring labor demand in markets not defined by standard industrial or occupational codes. Drawing from 84 million online help wanted postings, we create a dataset of 434, 000 health IT–related job listings from 2007 to 2011 whose descriptions contain key phrases such as "electronic health record" or "clinical informatics." We find that health IT–related job postings have grown substantially over time, tripling as a share of healthcare job postings since 2007. Trend‐break and difference‐in‐difference analyses suggest that health IT–related job postings accelerated following HITECH. According to our preferred specification, the legislation was associated with an 86 percent increase in monthly postings, or 162, 000 additional postings overall.